Draft genome sequence of Komagataeibacter rhaeticus Strain AF1, a high producer of cellulose, isolated from kombucha tea - Santos, Renato Augusto Corrêa dos; Berretta, Andresa A.; Barud, Hernane da Silva [UNESP]; Ribeiro, Sidney José Lima [UNESP]; González-García, Laura Natalia; Zucchi, Tiago Domingues; Goldman, Gustavo H.; Riaño-Pachón, Diego M. (Genome Announcements, 2014)
Here, we present the draft genome sequence of Komagatabaeicter rhaeticus strain AF1, which was isolated from Kombucha tea and is capable of producing high levels of cellulose.